Perlindungan Konsumen Pengguna Jasa Angkutan Penumpang PT. MRT Jakarta Ditinjau Dari Peraturan Perundang Undangan - Churniawan, Erifendi; handoko, handoko; darmawan, endras setiyo (Politeknik Perkeretaapian Indonesia Madiun, 2019)
This study aims to determine whether the Consumer Protection Act has provided legal protection for users of Jakarta MRT transportation services. Besides that, it is also to find out how far the MRT Jakarta is in handling operational disruptions that cause harm to passengers. This research is a descriptive normative legal research. This research uses a qualitative approach. Types of legal materials that are secondary legal materials. In this research, the techniques of collecting legal materials are collected namely: library research and cyber media. In analyzing this legal material the writer uses descriptive qualitative methods. Based on the research, it was obtained that the Consumer Protection Act has provided legal protection for Jakarta MRT transport passengers. The Consumer Protection Act that applies in the provisions described in the regulation is the obligation of the railroad implementing agency namely PT. MRT Jakarta in the event of an interruption is evacuating, refunding and securing equipment in accordance with security and safety aspects.